A longitudinal exploration of self-reported TV behaviours as a surrogate for sedentary behaviour in older adults with an intellectual disability from the intellectual disability supplement to the Irish longitudinal study on aging (IDS-TILDA) study - Lynch, Louise Annmarie; Mc Carron, Mary; Burke, Eilish (My University, 2024)
This study presents the findings of an investigation into the self-reported TV habits of adults with an intellectual disability, where time watching TV was used as a proxy for sedentary behaviour (SB). Risk factors identified for the general and intellectual disability populations and standard covariates of age, sex, level of intellectual disability, living circumstances and BMI were explored to determine their viability as contributors to increased TV viewing and SB. Missing data was imputed using Multiple Imputation Chained Equation (MICE). Multinomial logistic regression and Chi-squared Automatic Interaction Detector Analysis (CHAID) were explored and compared. The Systems of Sedentary Behaviour framework was used to structure results. Novel risk factors for increased TV viewing were identified.
PUBLISHED
https://doi.org/10.1177/17446295241230578
Keywords: Sedentary behaviour, TV, health, intellectual disability; Ageing; Clinical learning environment in nursing; Health attitudes and behaviour; Health outcomes; Health status and inequalities; Intellectual Disability; OLDER PEOPLE; Public health; Autistic Spectrum disorders; Intellectual Disability; Health